Radiographic features of staphylococcal pneumonia in adults and children. - Macfarlane, J. (1996)
BACKGROUND: Clinical and laboratory features do not accurately correlate with the cause of community acquired pneumonia. A study was performed to examine whether the radiographic features of staphylococcal pneumonia are sufficiently distinct to aid early diagnosis. METHODS: The chest radiographs of 34 patients (including eight children) with proven staphylococcal pneumonia were reviewed by two experienced observers using methods described previously. Features on presentation and follow up were noted. RESULTS: The most striking features were the presence of multilobar consolidation on presentation, cavitation, pneumatocoeles and spontaneous pneumothorax, together with a tendency to radiographic deterioration after admission in both adults and children. Some of these features are much less common with other causes of community acquired pneumonia. However, most of the cases did not have these classic features. CONCLUSIONS: The presence of certain radiographic features, including multilobar shadowing, cavitation, pneumatocoeles, and spontaneous pneumothorax, are seen with staphylococcal pneumonia in adults and children, but their absence does not exclude the diagnosis.